PWE-140 Persistent symptoms following cholecystectomy is unacceptably high and in need of further evaluation. (28th May 2012) - Radwan, R; Brown, C; Rasheed, A
Abstract : Introduction: Up to 20% of patients undergoing cholecystectomy continue to experience symptoms. We consider such results unacceptably high and in need of further evaluation. Our aim was to identify the biliary symptoms for which cholecystectomy was carried out and then determine the prevalence and the nature of persistent symptoms following the procedure in a cohort of 500 consecutive cases. Methods: A validated pre-operative symptoms survey was completed at the time of listing of 500 consecutive laparoscopic cholecystectomies (LC), followed by a follow-up phone survey 12 weeks after the procedure to record the nature, severity and frequency of symptoms experienced pre- and post-operatively. A detailed clinical profiling was carried out on all patients with persistent biliary symptoms. Results: All patients had at least two symptoms pre-operatively and 337 (67.4%) had three or more. The most common symptoms pre-operatively were abdominal pain (93.8%), nausea (65.8%), pain related to food (54.4%) and bloating (48.6%). A total of 90 patients were symptomatic postoperatively. 81 patients (16.2%) complained of abdominal pain, while 63 (12.6%) patients also experienced associated dyspeptic symptoms. Seventy three patients (14.6%) developed one or more new symptoms post-operatively, the most common being heartburn found in 34 (6.8%) and abdominal bloating in 29 (5.8%). 60 patients underwent further investigation following LC; 36 patients went on to have a secondary diagnosis made, the most common (13/36) being hiatus hernia, seven patients were found to have a retained common bile duct stone. Overall, there was no significant difference in histology among patients post-operatively. Conclusion: A significant number of patients continue to experience symptoms following laparoscopic cholecystectomy. In patients where pain was the most troublesome symptom preoperatively, significant symptomatic improvement was noted. Similarly, those patients that experienced symptoms more dyspeptic in nature preoperatively were less likely to be symptom free following LC. A careful biliary history, a focused physical examination and a thorough pre-operative assessment must be carried out prior to LC to rule out conditions that masquerade as gallbladder disease. Competing interests: None declared.